The Interpretations of Morality and Ideology in Wes Anderson’s Film Isle of Dogs - Riza, Dwi Ainur; Oktavia, Dian; Pasopati, Rommel Utungga; Andharu, Devito; Fadillah, Muhammad Reza Ishadi (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2025)
This study aims to explore the interpretations of morality and ideology in Wes Anderson's film Isle of Dogs. The research employs a qualitative method with the data collection technique of note-taking by watching the film, noting the dialogues of scenes related to the themes of morality and ideology. Data analysis is conducted by examining the characters and plot of the film in relation to the concepts of morality and ideology based on ethical theories and structuralism of ideology. Morality in this film reflects the tension between individual values and collective decisions in society, while ideology is portrayed as a system of power that dominates political decisions. Through the analysis of morality and ideology, it is found that the characters in the film are caught in a conflict between actions that are considered morally right and the ideologies they follow. The film critiques social and political structures through the messages conveyed by characters like Mayor Kobayashi and Chief, who represent a larger system of power. In conclusion, this analysis highlights how the moral messages in the film are connected to ideological decisions that can either worsen or improve the state of society.